2017
DOI: 10.1080/15481603.2017.1287838
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring drought vulnerability using multispectral indices observed from sequential remote sensing (Case Study: Tuy Phong, Binh Thuan, Vietnam)

Abstract: This study applies multispectral band ratios to examine vegetation density and vegetation health to assess drought conditions over nearly 30 years in Tuy Phong district, Binh Thuan province, Vietnam using a sequence of Landsat imagery (TM and OLI). Our research area has a distinctive climate, characterized by arid and semiarid areas adjacent to Binh Thuan's coastline. Drought is likely intensified by rain shadow effects of the Central Highlands (part of the Truong Son-or the Annamese Cordillera, positioned im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 17 publications
0
31
0
2
Order By: Relevance
“…Upon local reports, during the 2014-2015 dry season, there was a significant decline of water in the main reservoirs; in 2015, Da Bac Lake lost 90% of its fresh water [16]. Our recent study of agricultural drought severity in Tuy Phong district under a scenario of rainfall shortage indicated that those coastal communes are sensitive subjects to drought at moderate to mild levels [17], which are shown in light green to yellow in Figure 4. The analysis of that study was based on an idea of using the Vegetation Health Index (VHI) extracted from satellite images [18], which are Landsat time series data to access spatial and temporal agricultural drought patterns in Tuy Phong.…”
Section: Study Area Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon local reports, during the 2014-2015 dry season, there was a significant decline of water in the main reservoirs; in 2015, Da Bac Lake lost 90% of its fresh water [16]. Our recent study of agricultural drought severity in Tuy Phong district under a scenario of rainfall shortage indicated that those coastal communes are sensitive subjects to drought at moderate to mild levels [17], which are shown in light green to yellow in Figure 4. The analysis of that study was based on an idea of using the Vegetation Health Index (VHI) extracted from satellite images [18], which are Landsat time series data to access spatial and temporal agricultural drought patterns in Tuy Phong.…”
Section: Study Area Backgroundmentioning
confidence: 99%
“…The study area was indicated under moderate to mild impact of drought. The analysis was based on assessing spatial and temporal Vegetation Health Index distribution via Landsat images over 27 years [17].…”
Section: Study Area Backgroundmentioning
confidence: 99%
“…Under these conditions in which precipitation decreases and the temperature increases, semi-arid zones can face large water losses due to high evapotranspiration and aggravate scarcity [16]. Remote-sensing products such as NDVI and LST have proven to be valuable proxies for monitoring vegetation dynamics [17], land surface moisture conditions [18], yield estimates [19], soil evaporation rates [20], and drought vulnerability [21]. In the context of generating early alert systems, various spectral indexes have been developed for monitoring droughts, such as the Vegetation Temperature Condition Index-VTCI [22,23], the Vegetation Supply Water Index-VSWI [24] or the Soil Moisture Agricultural Drought Index-SMADI [25] among others.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between LST and NDVI has been generally described as having a negative correlation (e.g., Refs. [21,26]) with steeper slopes for dryer conditions [25]. However, the relationship between LST and NDVI may exhibit notable spatial [27] and temporal [26] alterations, and new research is needed in order to assess the sensitivity and resilience of ecosystems to climate variability [28].…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological drought occurs due to a deficit of precipitation, which brings about a shortage of available soil water for plant growth [4][5][6]. Agricultural drought is caused by the shortage of soil water, which results in significant damage to agricultural ecosystems (e.g., crop yield) [7][8][9]. Hydrological drought refers to groundwater depletion and the lack of surface water, which affects water resources for allocation [10].…”
Section: Introductionmentioning
confidence: 99%